2001
DOI: 10.1021/jp004269g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Polymerization of n-Butyl Vinyl Ether Initiated by Dichloroalane (AlHCl2):  A New Cationic Initiating System

Abstract: The carbocationic polymerization of n-butyl vinyl ether (BVE) using the new LiAlH4/AlCl3 initiating system is reported. The polymerizations were carried out in diethyl ether (Et2O), and in a mixture of diethyl ether and dichloromethane (1:1 v/v) at various temperatures, and the kinetics of the polymerizations was studied. The rate constants, the temperature dependence of the rate constants, and the kinetic order of the reactants were determined. The end groups of the polymers were characterized by 1H NMR and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…The CH protons (p) of VBE backbone and CH 2 protons (k) of VBE substituent resonate at δ = 3.09 ppm and 3.27 ppm, respectively. These data are also in good agreement with those obtained by Keki et al61…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The CH protons (p) of VBE backbone and CH 2 protons (k) of VBE substituent resonate at δ = 3.09 ppm and 3.27 ppm, respectively. These data are also in good agreement with those obtained by Keki et al61…”
Section: Resultssupporting
confidence: 93%
“…Figure 3 shows a 13 C NMR spectrum of PHEA and HEA–VBE with complete assignments of the chemical shifts. The spectral data are in a good agreement with the data of Keki et al,61 who reported the spectral features of poly(butyl vinyl ether).…”
Section: Resultssupporting
confidence: 90%
“…The control experiments with MAO as an initiator did not yield any polymer in any instance, whereas EtAlCl 2 as an initiator yielded PVEs having molecular weights of 5000–6000 g mol −1 but were atactic in nature. This observation was similar to that of cationic polymerization using AlHCl 2 which yielded poly( n ‐butylvinyl ether) (PBVE) having molecular weights of 3000–12 000 g mol −1 and polydispersity index (PDI) of 1.5 28…”
Section: Resultssupporting
confidence: 77%
“…*: Also predicted to be layered by supervised SVM. † : Sn 2 Ge: Reported to phase-separate at high Sn concentrations;28 CuI 2 : reported to be unstable; 29 MgHF: there have been studies on the Mg−H−F system that may suggest solubility problems;30 AlHCl 2 : reported to be a molecular species 31.…”
mentioning
confidence: 99%